The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0317167100006028
|View full text |Cite
|
Sign up to set email alerts
|

Headache During Gestation: Evaluation of 1101 Women

Abstract: Primary headache such as tension type headache and migraine may occur during pregnancy 1,2,3 either as a recurrent symptom of a previous condition or as a new onset manifestation.Secondary headache that mimics migraine may occur in the gestational period. 2,3 This type of headache may be caused by vasculitis, cerebral tumor, choriocarcinoma, pituitary tumor, arteriovenous malformation, sinus disorders, idiopathic intracranial hypertension, subarachnoid hemorrhage, cerebral arterial and venous episodes, pre-ecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
53
0
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 17 publications
8
53
0
13
Order By: Relevance
“…The majority of epidemiological studies demonstrate that pregnant women suffering from headaches prior to pregnancy report an improvement ranging from 55 to 90 % of cases [5]; in our study, we found an improvement in 60 % of cases (375/620) and the total disappearance of attacks in 195 cases (31 %). With regard to the total disappearance of headache in pregnancy, if we consider only those women classified as Definite migraine (n = 303), 27 % of them (n = 81) show complete disappearance of the attacks.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The majority of epidemiological studies demonstrate that pregnant women suffering from headaches prior to pregnancy report an improvement ranging from 55 to 90 % of cases [5]; in our study, we found an improvement in 60 % of cases (375/620) and the total disappearance of attacks in 195 cases (31 %). With regard to the total disappearance of headache in pregnancy, if we consider only those women classified as Definite migraine (n = 303), 27 % of them (n = 81) show complete disappearance of the attacks.…”
Section: Discussionsupporting
confidence: 62%
“…However, some of these cases may have been caused by secondary headaches, in particular those linked to hypertensive disorders [5,8]. In fact, our data did not allow us to investigate this aspect.…”
Section: Discussionmentioning
confidence: 71%
“…Melhado et al 3 conducted a large prospective study of 1,029 pregnant women in a variety of obstetrical settings, also utilizing International Headache Society classification. 21 Although they did not focus on acute severe headache, a subgroup of 76 women experienced new-onset or a new type of headache in pregnancy, of whom 52.6% had secondary headache.…”
Section: Discussionmentioning
confidence: 99%
“…2 Migraine is the most common disabling primary headache disorder, and, in pregnancy, retrospective and prospective studies consistently demonstrate that by the second trimester, migraine frequency typically improves, although attacks of migraine with aura and aura without headache may not reflect this pattern. [3][4][5][6][7][8][9][10] Acute, severe headache in pregnancy is generally regarded as a "red flag" and a cause for further investigation, particularly when new onset. [11][12][13] Various secondary headache disorders are more likely to occur during this time period, 12 possibly related to hypercoagulability, hormonal factors, anesthesia for labor, and other mechanisms.…”
mentioning
confidence: 99%
“…The improvement we found is as previously observed with migraine headaches. [15][16][17] While it is agreed that there is a wide migraine improvement rate of 18-80% in different studies, 14 our finding of migraine improvement rate of 100% is most likely due to the relatively small sample size of our survey. We equally noted a high improvement rate of 82.5% for TTH.…”
Section: Discussionmentioning
confidence: 97%